The Impact of the Use of Wearable Video Systems in Law Enforcement - Hoard, DeAris Vontae (2019)
Wearable video systems (WVSs) are one of the most popular and fastest growing technologies used by law enforcement today. While published WVS literature predominantly focuses on stakeholder perceptions, community interactions, assaults against officers, and use of force, there has diminutive exploration of the impact of WVSs as it related to aspects of police misconduct, especially in the Cruiser Police Department (pseudonym; CPD). The purpose of this mixed methods study was to explore and describe how the use of the use of WVSs by the CPD impact police misconduct, by tracking the changes in complaint type and disposition of a 5-year period, and to examine how CPD officers perceive the impact of the use of WVSs. Deterrence theory and phenomenology provided structure for this research study. The quantitative portion of this study consisted of an interrupted time series analysis of 419 documented complaints against CPD officers between June 2013 and June 2018. The qualitative portion consisted of 67 anonymous, online surveys completed by current CPD officers with WVS experience that were thematically analyzed. Quantitative findings included a 13% overall increase in the number of complaints, a 15% drop in citizen complaints, a 28% increase in chief-initiated complaints, and a 41% increase in sustained complaints. Qualitative findings provided insight into CPD officers' acceptance and value of WVS, along with their strong concern for WVSs implementation creating more discipline of officers. Implications for positive social change include an awareness of unintended consequences of current policies and practices and empirical awareness of trends associated with WVS, specifically regarding discipline, officer acceptance, and police-community interaction